Informal funds transfer systems : an analysis of the informal Hawala System - El Qorchi, Mohammed...[et al.] (IMF WashingtonUS, 2003)
Presents the findings, analyses and conclusions of a study on the operational characteristics of informal 'hawala' which is used predominantly in the Middle East and South Asia.